Photonics modelling and design - Sujecki, Slawomir (Optical sciences and applications of light, 2015)
Photonics Modeling and Design delivers a concise introduction to the modeling and design of photonic devices. Assuming a general knowledge of photonics and the operating principles of fibre and semiconductor lasers, this book:Describes the analysis of the light propagation in dielectric mediaDiscusses heat diffusion and carrier transport Applies the presented theory to develop fibre and semiconductor laser models.